Antinociceptive and anti-inflammatory effects of stachytarpheta jamaicensis (L.) Vahl (Verbenaceae)in experimental animal models. - Sulaiman, Mohd Roslan; Zakaria, Zainul Amiruddin; Chiong, Hoe Siong; Lai, Sook Kean; Israf Ali, Daud Ahmad; Tengku Mohamad, Tengku Azam Shah (Karger, 2009)
Objective: The present study was carried out to explore the antinociceptive as well as the anti-inflammatory effects of an ethanol extract of Stachytarpheta jamaicensis (L.) Vahl (EESJ) using 3 models of nociception and 2 models of inflammation in experimental animals.